Generation of Marker- and/or Backbone-Free Transgenic Wheat Plants via Agrobacterium-Mediated Transformation - Wang, Gen-Ping; Yu, Xiu-Dao; Sun, Yong-Wei; Jones, Huw D.; Xia, Lan-Qin (Frontiers in Plant Science, 2016)
Horizontal transfer of antibiotic resistance genes to animals and vertical transfer of herbicide resistance genes to the weedy relatives are perceived as major biosafety concerns in genetically modified (GM) crops. In this study, five novel vectors which used gusA and bar as a reporter gene and a selection marker gene, respectively, were constructed based on the pCLEAN dual binary vector system. Among these vectors, 1G7B and 5G7B carried two T-DNAs located on two respective plasmids with 5G7B possessing an additional virGwt gene. 5LBTG154 and 5TGTB154 carried two T-DNAs in the target plasmid with either one or double right borders, and 5BTG154 carried the selectable marker gene on the backbone outside of the T-DNA left border in the target plasmid. In addition, 5BTG154, 5LBTG154 and 5TGTB154 used pAL154 as a helper plasmid which contains Komari fragment to facilitate transformation. These five dual binary vector combinations were transformed into Agrobacterium strain AGL1 and used to transform durum wheat cv Stewart 63. Evaluation of the co-transformation efficiencies, the frequencies of marker-free transgenic plants and integration of backbone sequences in the obtained transgenic lines indicated that two vectors (5G7B and 5TGTB154) were more efficient in generating marker-free transgenic wheat plants with no or minimal integration of backbone sequences in the wheat genome. The vector series developed in this study for generation of marker- and/or backbone-free transgenic wheat plants via Agrobacterium-mediated transformation will be useful to facilitate the creation of ‘clean’ GM wheat containing only the foreign genes of agronomic importance.